Intestinal-type adenocarcinoma of the vulva: A case study - Brian Kaltenecker; Robert Manos; Meagan McCall; Paul Sparzak (Elsevier, 2019)
Approximately 5% of all gynecologic cancers are of the vulva, of which 90% are squamous cell in origin. Adenocarcinomas of the vulva are extremely infrequent with most relating to epithelial glands in the vulvar region. A 53 year old African American female presented to the emergency department complaining of a lesion on her left labia that had been present for the past 6 months. In the operating room, multiple biopsies were taken of the left labial lesion as well as the right, and sufficient tissue was sent to pathology for analysis. The pathology report demonstrated adenocarcinoma of the vulva with intestinal type features, CD20+, CK7-, mCEA+, vimentin -, p53+. These findings were consistent with a colorectal primary; however, no colorectal primary was discovered. The intestinal type of primary adenocarcinoma of the vulva is a rare variant, and only a few cases have been reported to date. It histologically resembles mucinous colonic carcinomas, but immunohistochemical workups with various tumor markers are needed before confirmation. Keywords: Adenocarcinoma, Oncology, Vulvar carcinoma, Vulvar cancer, Gynecology